Contribution of pre-existing neoantigen-specific T cells to a durable complete response after tumor-pulsed dendritic cell vaccine plus nivolumab therapy in a patient with metastatic salivary duct carcinoma. (4th July 2022) - Ichimiya, Shu; Fujimura, Akiko; Masuda, Muneyuki; Masuda, Shogo; Yasumatsu, Ryuji; Umebayashi, Masayo; Tanaka, Hiroto; Koya, Norihiro; Nakagawa, Shinichiro; Yew, Poh Yin; Yoshimura, Sachiko; Onishi, Hideya; et al.
ABSTRACT: Although immune checkpoint inhibitors (ICIs) have emerged as new therapeutic options for refractory cancer, they are only effective in select patients. Tumor antigen-pulsed dendritic cell (DC) vaccine therapy activates tumor-specific cytotoxic T lymphocytes, making it an important immunotherapeutic strategy. Salivary ductal carcinoma (SDC) carries a poor prognosis, including poor long-term survival after metastasis or recurrence. In this study, we reported a case of refractory metastatic SDC that was treated with a tumor lysate-pulsed DC vaccine followed by a single injection of low-dose nivolumab, and a durable complete response was achieved. We retrospectively analyzed the immunological factors that contributed to these long-lasting clinical effects. First, we performed neoantigen analysis using resected metastatic tumor specimens obtained before treatment. We found that the tumor had 256 non-synonymous mutations and 669 class I high-affinity binding neoantigen peptides. Using synthetic neoantigen peptides and ELISpot analysis, we found that peripheral blood mononuclear leukocytes cryopreserved before treatment contained pre-existing neoantigen-specific T cells, and the cells obtained after treatment exhibited greater reactivity to neoantigens than those obtained before treatment. Our results collectively suggest that the rapid and long-lasting effect of this combination therapy in our patient may have resulted from the presence of pre-existing neoantigen-specific T cells and stimulation and expansion of those cells following tumor lysate-pulsed DC vaccine and ICI therapy.